2008
DOI: 10.1029/2007gb002984
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting atmospheric dust export to the Southern Hemisphere ocean: Biogeochemical implications

Abstract: [1] Aerosol concentrations in the Southern Hemisphere are largely undersampled. This study presents a chemical and physical description of dust particles collected on board research vessels in the southeast Pacific (SEPS) and the Southern Ocean (SOKS). Concentrations of dust were 6.1 ± 2.4 ng m À3 for SEPS and 13.0 ± 6.3 ng m À3 for SOKS. Dust fluxes, derived from those concentrations, were 9.9 ± 3.7 mg m À2 d À1 for SEPS and 38 ± 14 mg m À2 d À1 for SOKS and are shown to be representative of actual fluxes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
202
9

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(242 citation statements)
references
References 80 publications
31
202
9
Order By: Relevance
“…Diazotrophs have higher requirements for iron than non-diazotrophic primary producers. Hence, the low iron inputs to the SPG, as a result of the remoteness of the SPG to any continents, may ultimately limit N 2 -fixation (Wagener et al, 2008). A recent study (Mohr et al, 2010) showed that the method used here would likely have underestimated N 2 -fixation rates in the SPG.…”
Section: Resultsmentioning
confidence: 99%
“…Diazotrophs have higher requirements for iron than non-diazotrophic primary producers. Hence, the low iron inputs to the SPG, as a result of the remoteness of the SPG to any continents, may ultimately limit N 2 -fixation (Wagener et al, 2008). A recent study (Mohr et al, 2010) showed that the method used here would likely have underestimated N 2 -fixation rates in the SPG.…”
Section: Resultsmentioning
confidence: 99%
“…[26] The higher concentrations of chlorophyll are likely related to the input of dust from Patagonia into the Atlantic sector, especially in the west [Mahowald et al, 1999;Wagener et al, 2008], and thus of the often-limiting micronutrient, iron; large parts of the Pacific and Indian sectors, too distantly removed from any such dust source, are likely to be significantly more iron limited than the Atlantic sector. Iron enrichment experiments in the Southern Ocean indicate that inputs of iron to surface waters here shifts the structure of the phytoplankton community toward domination by large diatoms (Fragilariopsis, Thalassiothrix, and Odontella spp.…”
Section: Resultsmentioning
confidence: 99%
“…All three core positions are located south of the present-day Antarctic Polar Front (APF) and were chosen to represent different environmental conditions during both the Holocene and the last glacial, especially in term of sea ice coverage. The site from the Scotia Sea (Atlantic sector) is the site which is closest to the sea ice edge and currently has the highest amount of dust [Wagener et al, 2008] and chlorophyll ( Figure 2) compared to the sites from the Indian and Pacific sectors.…”
Section: Sediment Coresmentioning
confidence: 99%
“…We calculate oxygen solubility from atmospheric pressure, temperature, and salinity measurements (Garcia and Gordon, 1992). The piston velocity for oxygen is estimated from the NCEP/NCAR windspeed reanalysis data product (Kalnay et al, 1996) and the parameterization of Wanninkhof (Wanninkhof, 1992). Piston velocity is weighted for windspeed history at the collection site (Reuer et al, 2007).…”
Section: O 2 /Ar Measurementsmentioning
confidence: 99%
“…Atmospheric Fe deposition was estimated following a method recently described (Wagener et al, 2008). See for a description of the dissolved Fe budget, including the atmospheric Fe deposition measurements, during the SAZ Sense cruise.…”
Section: Ancillary Measurementsmentioning
confidence: 99%